Efektivitas Pelatihan Regulasi Emosi terhadap Penyesuaian Diri Anak Asuh LKSA di Kota Padang - Assyifaa Herbi Nuari; Rizal Kurniawan; Rusmen Rusmen; Hanifa Laura Dalimunthe (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
This study aimed to examine the effectiveness of emotion regulation training in improving the adjustment of adolescents living in orphan in Padang. The research employed a mixed method approach using a one group pre-test post-test experimental design supported by qualitative data. Participants were 26 adolescents from one orphan in Padang. Data were collected through an adjustment scale administered before and after the intervention, observation, and open-ended questionnaire  questionnaire  responses. Quantitative data were analyzed using the Wilcoxon Signed Rank Test with the assistance of IBM SPSS 23, while qualitative data were analyzed through thematic analysis using NVivo 12. The results showed a significant difference between pre-test and post-test scores, indicating an improvement in overall adjustment after the training. Most participants experienced increased scores across emotional maturity, intellectual maturity, social maturity, and responsibility. Qualitative findings revealed positive behavioral changes, including helping behavior, cooperation, rule compliance, and independent problem solving. These findings indicate that emotion regulation training is effective in enhancing adolescents adjustment in institutional care settings.